Corporate ESG implementation and firm success: An empirical study in the Asian Markets. - Shamsudin, Siti Marlia; Mohd Suffian, Mohd Taufik; Liyana Ab Rahman; Masetah Ahmad Tarmizi (International Journal of Accounting, Finance and Business, 2025)
This study investigates the effect of ESG dimensions on the financial outcome of companies across six selected Asian markets. The sample from this study was downloaded from LSEG, which consists of 418 non-financial listed firms in six Asian countries over the period 2019 to 2024. A linear regression analysis was conducted to examine the correlation between the ESG score and financial variables concerning Return on Assets (ROA) and Return on Equity (ROE). The findings reveal that firm performance is positively affected by ESG performance using both financial indicators, ROA and ROE. This indicates that firms with good ESG performance will have better performance, which is in line with the purpose of the implementation of ESG itself: to create business value and fair governance while protecting the Earth. On the contrary, the control variables, such as firm size and leverage, show significant adverse effects, indicating that poor operational efficiency or high financial burden may weaken the firm's financial performance. These findings have offered a new regional perspective on the implications of ESG towards Asian firm performance. This is important as investors and regulators are looking to align financial goals with corporate sustainability requirements.